Characterization of diffuse lung function in children with Mycoplasma pneumoniae pneumonia - Wang, Li; Li, Qianqian; Hu, Jie; Luo, Ronghua; Duan, Yaping; Ai, Tao (Frontiers in Pediatrics, 2025)
BackgroundMycoplasma pneumoniae infection accounts for a high proportion of community-acquired pneumonia and the incidence rate of severe M. pneumoniae pneumonia (MPP) has increased year by year. This study investigated the changes in lung diffusion function after M. pneumoniae infection, compared the lung diffusion and ventilation function of children with mild (MMPP) or severe M. pneumoniae pneumonia (SMPP) infections, and explored their clinical significance.ObjectiveTo study the changes in pulmonary ventilation and pulmonary diffusion function in children with MPP, and explore their clinical significance.MethodsData from 97 children with M. pneumoniae pneumonia hospitalized in Chengdu Women and Children's Central Hospital from June 2023 to December 2023 were collected and the participants were divided into an MMPP group (n = 44) and an SMPP group (n = 53). The changes in pulmonary ventilation function and diffusion function were compared between the two groups.ResultsThe Z-scores of forced vital capacity and forced expiratory volume in the first second in the SMPP and MMPP groups were −1.684 ± 0.902 and −1.986 ± 0.818, and 0.164 ± 1.795 and −0.6104 ± 1.276, respectively. In the SMPP group, the two aforementioned indicators were lower than the normal value and significantly lower than those in the MMPP group (P < 0.001). The carbon monoxide diffusion capacity in the SMPP group (−5.931 ± 0.827) was significantly lower than that in the MMPP group (−5.0775 ± 1.1134) (P < 0.001). The forced expiratory flow at 75% vital capacity and the maximum mid expiratory flow in the SMPP group were −2.006 ± 1.2582 and −1.878 ± 1.008, respectively, which were lower than the normal value.ConclusionSMPP results in more severe ventilation dysfunction and diffuse dysfunction than MMPP.